AGAMA SEBAGAI ALAT HEGEMONI DALAM KEKERASAN DOMESTIK PERSPEKTIF ANTONIO GRAMSCI - Ifan Hanafi (Jurnal Harkat : Media Komunikasi Gender, 2023)
Abstract. Domestic violence is difficult to resolve because this case in private area. Cases of domestic violence released by the Indonesian Ministry of Women Empowerment and Child Protection in 2021 reached 25,210 cases where women were victims. The percentage of these cases as much as 57.8% of violence occurred in the house which is domestic violence. From this number, it is assumed that there are still many unsolved cases. In some cases women feel willing and feel deserving of acceptance. To launch their actions, the husband as the dominant party often uses verses from the Qur'an to legitimize the violence committed. The wife as a subordinate party, psychologically has been locked to provide resistance. This is what Antonio Gramsci calls hegemony. The hegemony theory says that the leader who becomes dominant to pressure subordinates uses consensus or text so that his power will last because there is an agreement between the two parties. Through this theory, it will be able to map out the inaccurate interpretation of religion that is often used by husbands in carrying out domestic violence in the family. Use of QS. An-Nisa' verse 34 by the husband as the dominant party can subordinate the wife to do nuzyuz, namely by beating. With the understanding of this verse, the subordinate or the wife will eventually feel that the husband's actions are worthy of acceptance. Therefore, understanding of religion and understanding of gender needs to be instilled early or no later than before marriage. Abstrak. Kekerasan domestik sulit diselesaikan karena kasus ini mencakup wilayah yang privat. Kasus kekerasan domestik yang dirilis oleh Kemenppa RI pada tahun 2021 mencapai 25.210 kasus dimana perempuan sebagai korban. Persentase dari kasus tersebut sebanyak 57.8% kekerasan terjadi didalam rumah yang merupakan kekerasan domestik. Dari jumlah tersebut diasumsikan masih banyak kasus yang tidak terungkap. Dalam beberapa kasus perempuan merasa rela dan merasa pantas untuk menerima. Untuk melancarkan tindakannya, suami sebagai pihak dominan seringkali memakai ayat Al-Qur'an untuk legitimasi atas kekerasan yang dilakukan. Istri sebagai pihak subordinat, secara psikologis telah terkunci untuk memberikan perlawanan. Hal inilah yang oleh Antonio Gramsci disebut sebagai hegemoni. Teori hegemoni mengatakan bahwa pihak pemimpin yang menjadi dominan untuk menekan pihak subordinat menggunakan konsensus atau teks sehingga kekuasaannya akan langgeng karena terjadi persetujuan antara kedua belah pihak. Melalui teori ini akan mampu memetakan penafsiran agama yang kurang tepat yang seringkali digunakan oleh suami dalam melakukan kekerasan domestik dalam keluarga. Penggunaan QS. An-Nisa’ ayat 34 oleh suami sebagai pihak dominan dapat mengsubordinasi istri melakukan nuzyuz yakni dengan cara pemukulan. Dengan pemahaman ayat ini, pihak subordinat atau istri lama-lama akan merasa bahwa tindakan suami memang layak untuk diterima. Oleh karenanya pemahaman agama dan pemahaman gender perlu ditanamkan semenjak dini atau selambat-lambatnya sebelum menikah.